Books announced and noted (Quarterly Journal of Economics, 1897)
Books announced and noted Get access The Quarterly Journal of Economics, Volume 11, Issue 2, January 1897, Pages 211–212, https://doi.org/10.1093/qje/11.2.211 Published: 01 January 1897